A high-energy quinone-based all-solid-state sodium metal battery. (August 2019) - Chi, Xiaowei; Hao, Fang; Zhang, Jibo; Wu, Xiangwei; Zhang, Ye; Gheytani, Saman; Wen, Zhaoyin; Yao, Yan
Abstract: Redox-active organic electrode materials show great promise as an addition to inorganic electrode materials for grid-scale energy storage due to their ability to store various cations, moderate operating potentials, and relatively high theoretical specific capacities. However, most organic compounds when reduced suffer from dissolution in organic liquid electrolytes, resulting in poor cycling stability. Herein, we show for the first time an all-solid-state battery based on an oxide-based solid electrolyte, beta-alumina solid electrolyte (BASE), that not only enables stable cycling of an organic quinone-based compound (pyrene-4, 5, 9, 10-tetraone, PTO) with high specific energy (~900 Wh kg −1 ) at the material level but also demonstrates the best cycling stability (1000 h at 0.5 mA cm −2 ) with a sodium metal anode among any reported all-solid-state sodium metal batteries (ASSMBs). Anode-electrolyte interfacial resistance was successfully reduced by introducing a Sn thin film between the Na anode and BASE. The cathode-electrolyte interfacial barrier was overcome with a mechanically compliant PTO-poly(ethylene oxide)-carbon composite cathode that forms interpenetrating ionic and electronic pathways which favor full utilization of PTO. This proof-of-concept demonstration combining organic electrode materials with an oxide-based solid electrolyte and the interface modification strategies pave the way for ASSMBs with higher capacity and cycling stability. Graphical abstract: Image 1 Highlights: An all-solid-state Na metal battery with a quinone cathode is demonstrated. Nano Sn interlayer benefits the wetting and long cycling of Na metal (1000 h). Beta-alumina solid electrolyte effectively suppresses the dissolution of organic cathode. Pyrene-4, 5, 9, 10-tetraone cathode delivers the highest energy (ca. 900 Wh kg −1 ) at the material level.